Cep57, a multidomain protein with unique microtubule and centrosomal localization domains - Momotani, Ko (Biochem J, 2008)
This study demonstrates different functional domains of a recently described centrosomal protein, Cep57 (Centrosomal protein 57). Endogenous Cep57 protein and ectopic expression of full-length protein or the N-terminal coiled-coil domain localize to the centrosome internal to γ-tubulin suggesting that it is either on both centrioles or a centromatrix component. The N-terminus can also multimerize with the N-terminus of other Cep57 molecules. The C-terminus contains a second coiled-coil domain that directly binds to microtubules. This domain both nucleates and bundles microtubules in vitro. This activity was also seen in vivo, as overexpression of full-length Cep57 or the C-terminus generates nocodazole resistant microtubule cables in cells. Based on these findings, we propose that Cep57 serves as a link with its N-terminus anchored to the centriole or centromatrix and its C-terminus to microtubules.